Analysis of Coaches Work Culture Behavior in DIY Province - Trisnar Adi Prabowo; Endang Rini Sukamti; Ardiah Juita; Agus Sulastio; Ni Putu Nita Wijayanti; Ricky Susiono (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2023)
The purpose of this research is to analyze the coaches work cultural behavior in DIY province in the context of POPNAS 2023 (National Student Sports Week) Indonesia. The importance of this study is to evaluate the trainer's performance during the training periodization. This research uses survey method, its analysis uses quantitative descriptive. The sample of this research is 40 trainers consisting of 15 types of sports, these sports will be competed in the Indonesian POPNAS (National Student Sports Week). The research instrument was a questionnaire in the form of a Google form consisting of 24 statement items. The indicators of the coache work culture behavior are divided into attitudes toward work and behavior on time work. Test the validity of the instrument using Aiken's with a value of 0.898 and Cronbach's Alpha reliability test with a value of 0.791. The results of this study indicate that the cultural behavior of DIY provincial trainers shows the results of "very poor" 4 coaches (10%), "less" 7 coaches (17.5%), "enough" 21 coaches (52.5%), "Good" 6 coaches (15 %), “very good” 2 coaches (5%). Based on the results of research on work behavior, the work culture of DIY coaches is in the dominant category of "enough". Thus it can be an evaluation material for all levels of coaches and sports organizations about the importance of coach awareness and other support including sports institutions so that they pay more attention to coaches. Suggestions from this study so that research can be developed by adding samples or research variables. Because research that examines the work culture of coaches is still a little published.